In-Vitro Evaluation of Two Seal Materials on Enamel Demineralization - Gülçin Acun; Didem Nalbantgil; Tülin Arun (Galenos Yayinevi, 2009)
The purpose of this in-vitro study was to evaluate the effects of two different seal materials, Pro Seal™ and BisCover™ LV on enamel demineralization adjacent to orthodontic fixed appliances. Sixty noncarious extracted premolars were allocated to three groups of twenty each as Pro Seal™ and BisCover™ LV as the study and Transbond™ XT as the control group. After placing the brackets, the teeth were cycled through a deminerali-zation-remineralization procedure for 30 days. Demineralization of the enamel surface was evaluated quantitatively by cross-sectional microhardness testing. The results reveal that, demineralization in the Pro Seal™ group was significantly less than the other two groups. As for BisCover™ LV group, significantly smaller amount of demineralization was observed than the control group. Pro SealTM and BisCoverTM LV can be considered for use in clinic as an effective method to prevent or reduce demineralization during orthodontic treatment, especially in patients with poor oral hygiene.